The importance of the english language in the academic life and professional development of the professors of The University of El Salvador, main campus, 2017 - Hernández Salgado, Josué Nehemías; Herrera Barahona, Krissia Beatriz; Quintanilla Juárez, Julio César (2024)
This research is about finding out how important the mastery of the English language (reading, understanding, speaking, and writing) is for the professors of the University of El Salvador, Main Campus, a research carried out during the second semester of the academic year 2017. A convenience sample of 80 professors out of about 1110 professionals both men and women, were interviewed in their respective school and were asked 4 basic questions dealing with the pertinence of English in their area of work, the role of English for their professionalization, and what their belief was about English, in general. The results show that most of the professors believe English is an important language these days, but on an individual basis they say English is a tool that they can do without. Also, they said they have a positive attitude toward English. The most important finding is that very few professors have functional mastery of English, say to give lectures or presentations on their expertise in English or write academic articles for academic magazines edited in English. These results are very telling as the role in the professors academic and professional life is arguably of little pertinence. To strengthen the validity of this study, a bigger sample that includes professors from the other three campuses (Santa Ana, San Vicente, and San Miguel) might be used